Adventure sports and tourism at the beginning of the construction of Europe in the Pyrenees - André Suchet (Revue de Géographie Alpine)
Organised in the spring of 1993 on the border between France and Spain, the Pyrenees Adventure Games (les Jeux Pyrénéens de l’Aventure or los Juegos Pirenaicos de la Aventura), brought together more than 1,000 athletes from 26 countries and were attended by 21,000 visitors. An alternative Olympics of adventure and outdoor sports patronised by the IOC, the events took place in the Aure Valley in France (Hautes-Pyrénées) and in the Sobrarbe in Spain (Huesca province). This article analyses the governance of this international sports competition. More specifically, this case study will enable us to find out more about the conditions of organisation of a cross-border project in the early 1990s. What were the various political, social and cultural exchanges between the valleys in terms of sports and tourism in the Pyrenees? The results show that the French organisation and the Spanish organisation functioned side by side instead of working together on the field. This division in working enabled them to bypass the language problem. The cross-border dimension of these adventure Olympics in 1993 stemmed from pressure from the French regional planning agency, DATAR right from the beginning of the project, i.e. in October 1989, to be exact. This dimension made the 1993 Pyrenees Adventure Games a testimony to the new political Europe that was being built after 1989. This period was marked by the proactiveness of institutions, which far exceeded the motivations of the populations of the Union.